CELLULAR MECHANISMS OF POSTTRAUMATIC REGENERATION OF THE LIVER OF RANA RIDIBUNDA (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
There are results of morphological examination of the liver of Rana ridibunda that was done in different periods of time after partial hepatectomy. It is shown that the restorative reaction of the frogs liver after partial hepatectomy, as well as the reaction of the liver of mammals and birds, is characterized by hepatocytes nuclei and cytoplasm hypertrophy. In the dynamics of quantity changes of double-nuclei hepatocytes there was determined a common peculiarity between the liver of birds and the one of frogs, expressed in the increase of ploidy (number of double-nuclei) of cells during posttraumatic regeneration.